Radioiodine remnant ablation in papillary thyroid microcarcinoma: a meta-analysis. Issue 7 (July 2019) - Yang, Ting; Zheng, Shi-Yang; Jiao, Ju; Zou, Qiong; Zhang, Yong
Abstract : Background: The incidence of papillary thyroid microcarcinoma (PTMC) has been increasing sharply, the current statement about whether PTMC patients should undergo radioactive iodine (RAI) remnant ablation is still controversial, mainly because it is uncertain whether RAI treatment can reduce the recurrence rate. Objective: To evaluate the effectiveness of RAI remnant ablation for thyroid cancer-related outcomes of PTMC patients. Methods: We comprehensively searched PubMed, Cochrane Library, Scopus and Science Direct for studies that compared the effectiveness after total-thyroidectomy or near total-thyroidectomy, with or without RAI remnant ablation treatment. Random and fixed-effects meta-analytical models were used where indicated, and between-study heterogeneity was assessed. Results: Twenty-two studies, which included 8724 patients, met our search criteria and were assessed. For PTMC patients treated by total thyroidectomy or near-total thyroidectomy, the locoregional recurrence rates were 1.92 and 7.36% [risk ratio (RR)=0.45; 95% confidence interval (CI)=0.18–1.11; P =0.08] for patients with or without RAI treatment respectively, the distant metastasis rates were 1.39 and 2.46% (RR=0.64; 95% CI=0.28–1.48; P =0.30), and the thyroid cancer-related mortality rates were 0.98 and 1.76% (RR=0.68; 95% CI=0.22–2.09; P =0.50). Conclusion: For PTMC patients who have already treated by total thyroidectomy or near-total thyroidectomy, incremental RAI remnant ablation may significantly improve thyroid cancer-related outcomes.